(untitled) - Massy, Patricia (Tokyo, 1980)
This book introduces about living with beauty, from Ashes and Earth, something to carry, something to wear, with Yarns and Dyes, with Prayers and with Joy.
Keywords: Handicraft,Thủ công; Japan,Nhật Bản